Optimizing Reduced Graphene Oxide with Metallic Nanoparticles for Increasing the Efficiency of Proton Exchange Membrane Fuel Cells. Issue 1735 (19th December 2014) - Isseroff, Rebecca; Chen, Arthur; Blackburn, Lee; Lish, Justin; Han, Long Tao; Li, Hongfei; Rafailovich, Miriam
ABSTRACT: The oxidation of CO to CO2 is necessary in the operation of Proton Exchange Membrane Fuel Cells (PEMFCs) since even a small amount of CO that is formed when the PEMFC is operated under ambient conditions is sufficient to poison the Pt catalyst in the electrodes and degrade the performance. Operation using higher loads of Pt catalysts or increasing the purity of the H2 input gas significantly adds to the cost, adversely impacting the commercial development of PEMFCs. We combined graphene oxide (GO) with metallic salts and partially reduced the mixture with sodium borohydride, yielding a metallized form of partially reduced graphene oxide (prGO) platelets that remained in solution. When these platelets were coated on the Nafion membrane of a PEMFC, a 72% increase in the power output was observed, whereas a 62% increase was observed when the membrane was coated with partially reduced graphene oxide without the metallic salts. Results will be presented for AuGO/prGO, PtGO/prGO, and AuPtGO/prGO combinations.